Loyalty as a legitimizer of wage theft - Stanley, Matthew L. (Journal of business ethics, 2025)
Wage theft the underpayment or nonpayment of workers’ wages and benefits by employers - is pervasive in the US and abroad, adversely affecting the lives and livelihoods of millions of people annually. Although academics, advocacy groups, and investigative journalists have made advances in documenting the pervasiveness and severity of wage theft practices across states, nations, and industries, research has yet to identify and characterize the processes that make the public see such practices as legitimate. Across four well-powered studies (total N = 2291), we leverage theory and research on moral identity and on evolutionary approaches to moral values to investigate a possible underlying psychological antecedent of the judged legitimacy of wage theft. We propose that the value placed on a widely shared and moralized principle - loyalty - may (ironically) underlie the legitimization of wage theft practices. Although people often consider loyalty to be a positive moral principle or virtue that ought to be valued and exemplified in social and business relations, we find consistent evidence that placing more value on loyalty closely tracks stronger beliefs that wage theft practices are legitimate. Ultimately, differences in the valuation of loyalty may help to explain and predict judgments about the legitimacy of wage theft practices across individuals, groups, organizations, and cultures.